Covering America : a narrative history of a nation's journalism - Daly, Christopher B. (University of Massachusetts Press, 2012)
"Today many believe that American journalism is in crisis, with traditional sources of news under siege from a failing business model, a resurgence of partisanship, and a growing expectation that all information ought to be free. In Covering America, Christopher B. Daly places the current crisis within a much broader historical context, showing how it is only the latest in a series of transitions that have required journalists to devise new ways of plying their trade. Drawing on original research and synthesizing the latest scholarship, Daly traces the evolution of journalism in America from the early 1700s to the digital revolution of today. Analyzing the news business as a business, he identifies five major periods of journalism history, each marked by a different response to the recurrent conflicts that arise when a vital cultural institution is housed in a major private industry. Throughout his narrative history, Daly captures the ethos of journalism with engaging anecdotes, biographical portraits of key figures, and illuminating accounts of the coverage of major news events as well as the mundane realities of day-to-day reporting."--Jacket